1998
DOI: 10.1051/analusis:1998134
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the speciation and the biogeochemical processes affecting the mobility of selenium from a geological repository of radioactive wastesto the biosphere

Abstract: Abstract. In the scope of the studies carried out on the geological disposal of radioactive wastes, it is essential to assess the migration behaviour of long lived radionuclides as a function of the physicochemical conditions (pH, redox potential, temperature, pressure, ...), the nature of the host rocks and the chemical composition of the underground waters. In this study, we have considered the case of selenium which is an element of importance because of its long lived under its 79 Se isotope . A review … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
0
3

Year Published

1999
1999
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(57 citation statements)
references
References 43 publications
(127 reference statements)
1
53
0
3
Order By: Relevance
“…However, Wang et al [63] reported that fresh sub-bituminous PRB ash exhibited low leaching potential, which is consistent with Se in the selenite form; therefore, the field-derived data may indicate conversion from selenite to selenate from environmental exposure in the landfill. Though the reaction kinetics of the oxidation of selenite to selenate are not well-understood, this reaction appears to be a slow process [65]. Oxidation state may also explain the differences noted between fresh and weathered ash water-soluble Se concentrations.…”
Section: Treatment Effects On Extractable Fly-ash Propertiesmentioning
confidence: 99%
“…However, Wang et al [63] reported that fresh sub-bituminous PRB ash exhibited low leaching potential, which is consistent with Se in the selenite form; therefore, the field-derived data may indicate conversion from selenite to selenate from environmental exposure in the landfill. Though the reaction kinetics of the oxidation of selenite to selenate are not well-understood, this reaction appears to be a slow process [65]. Oxidation state may also explain the differences noted between fresh and weathered ash water-soluble Se concentrations.…”
Section: Treatment Effects On Extractable Fly-ash Propertiesmentioning
confidence: 99%
“…Il existe sous quatre états d'oxydation dans les milieux naturels : le séléniure Se -2 (II), le sélénium élémentaire Se (0), le sélénite SeO 3 2-(IV) et le séléniate SeO 4 2-(VI) (Seby et al, 1998). Dans la plupart des sols les formes sélénite SeO 3 2-et séléniate SeO 4 2-, sont les plus fréquentes.…”
Section: Séléniumunclassified
“…Le sélénium élémentaire reste relativement insoluble, alors que le séléniure précipite avec des éléments métalliques pour donner des composés de faible solubilité. En conditions fortement réductrices, le séléniure est l'espèce majoritaire et peut exister sous forme de précipités insolubles ou de très faible solubilité, en présence de cations métalliques (Seby et al, 1998). À ces formes peuvent s'ajouter, en proportions variables, des composés organiques : substituts d'acides aminés, e.g., sélénométhionéine, sélénocystéine et des composés volatils tels que le diméthylséléniure, noté DMSe, (CH 3 ) 2 Se et le diméthyldiséléniure, noté DMDSe, (CH 3 ) 2 Se (Frankenberger et Karlson, 1994 ;Jayaweera et Biggar, 1996 ;Seby et al, 1998).…”
Section: Séléniumunclassified
See 1 more Smart Citation
“…The usual techniques used in these studies included absorption spectrometry using both hydride generation in a quartz furnace and electrothermal atomization [1], differential pulse cathodic stripping voltammetry [2], high-performance liquid chromatography (HPLC) with online detection by inductively coupled mass spectrometry or flame atomic absorption spectrometry [3] and capillary electrophoresis [4]. The lack of enough sensitivity and selectivity of some of the methods used requires a preconcentration step, such as coprecipitation [5], adsorption on XAD-resin [6] or iron (III)-loaded Chelex-100 resin [7], functional resin [8,9], activated carbon [10,11], thiol cotton [12] and extraction [13], among others.…”
Section: Introductionmentioning
confidence: 99%